Factors affecting women's adjustment to postpartum changes: A narrative review - Mahboobeh Asadi; Mahnaz Noroozi; Mousa Alavi (Wolters Kluwer Medknow Publications, 2020)
Background: Postpartum period is associated with stress and pressure, and the woman must adjust herself to these changes. This study aimed to review the factors affecting women's adjustment to postpartum changes in conducted studies. Materials and Methods: This review was conducted by searching databases such as ISI Web of Science, Science Direct, Scopus, Cochrane, PubMed and Scientific Information Database (SID), Iranian Medical Articles Database (IranMedex), Iranian Research Institute for Information Science and Technology (IranDoc), and the Iranian Magazine Database (MagIran), as well as searching through Google Scholar (as a Web search engine) in December 2019. Publications from July 2004 to October 2019 were reviewed and limited to Persian and English. The keywords used included "Postpartum", "Women's needs", "Adjustment" and "Coping". After reviewing the articles, out of 60 original articles, 17 articles were selected for final evaluation. Results: Factors affecting adjustment to postpartum changes were divided into personal and social factors. Personal factors included previous experiences, coping styles and strategies, personality traits, self-efficacy and awareness, and social factors included family and relatives, healthcare providers, cultural context, and laws and regulations. Conclusions: Adjustment to postpartum changes depends on the personal and social factors that can interact with each other. Women's awareness enables them to use positive coping strategies in this critical situation. Educating women's spouse and family members can contribute to increase the women's social support. Additionally, the law support guarantees the implementation of many interventions in promoting the mother's health.